Murder at la Villette [large type] - Black, Cara, 1951- (Thorndike Press large print mystery, 2024)
"Aimee Leduc's ex Melac, her daughter's father, has been hounding her for weeks, pressuring her to move little Chloe to Brittany, threatening to take her to court for custody - all but stalking her. Harassed and fed up, Aimee has stopped taking his calls. That's why she doesn't know as she's leaving a client's office late one night that Melac is waiting for her by the Bassin de la Villette - where an assailant attacks him just in time for Aimee to find his still-bleeding body in the canal. Interrupted, the killer knocks Aimee unconscious and plants the bloody knife in her hands for the police to find. Now Aimee is in police custody, debilitated by her concussion, with overwhelming evidence working against her. She has to figure out who set Melac up - but he was a man with many pasts, a former homicide investigator and the target of criminal grudges. Cut off from her typical network and forced to operate under multiple layers of cover, Aimee must go deep into the underbelly of Paris's 1 ("--